The Relationship between Parental Knowledge and Behavior with the Severity of Pneumonia in Toddlers - Lale Nubya Nitzana; Wayan Sulaksmana Sandhi Parwata; Titi Pambudi Karuniawaty (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
Pneumonia is an illness that frequently affects young children and significantly influences their health and overall life quality, particularly in toddlers. This research seeks to explore how parental awareness and actions relate to the seriousness of pneumonia among toddlers at the Lingsar and Sigerongan Community Health Centers. This study is an observational analytic study with a cross-sectional research design using consecutive sampling. The study was conducted in the working area of the Lingsar and Sigerongan Community Health Centers, West Lombok with a research sample of 112 respondents. The information collected was examined using the Spearman's rho test. The findings indicated that a majority of the parents of toddlers were aged between 20 and 35 years (83.9%), were predominantly female (51.5%), had low levels of education (51.8%), and the majority worked as housewives (74.1%). The data also showed that there was a high level of knowledge (80.4%) and positive behavior (96.4%). The analysis of the knowledge and behavior data through the Spearman's rho test yielded results of (p = 0.807) and (p = 0.292), indicating no significant correlation between parental knowledge and behavior with the severity of pneumonia in toddlers (p > 0.05). Furthermore, there was no significant link found between the history of basic vaccinations, nutritional status, family smoking background, exclusive breastfeeding history, low birth weight history, prematurity, and environmental factors with the severity of pneumonia in toddlers. There was no association between parental knowledge and behavior and the severity of pneumonia in toddlers at the Lingsar and Sigerongan Health Centers in West Lombok.